Analisis Persepsi Mahasiswa Terhadap Kawasan Tanpa Rokok Sebagai Manifestasi Hak Atas Kesehatan (Studi Kasus: Mahasiswa Pendidikan Biologi Kelas A) - Sinaga, Vanesia Syhana EZ; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Adilla, Ananda; Harahap, Amelia Patra; Salya, Vina; Sitompul, Jelita Geovani; Br Tarigan, Puspita Sari (Innovative: Journal Of Social Science Research, 2024)
Based on data, the prevalence of active smokers in Indonesia continues to increase. Data from the 2023 Indonesian Health Survey (SKI) conducted by the Ministry of Health (Kemenkes) shows that the number of active smokers is estimated to reach 70 million people, with 7.4% of them aged 10-18 years. This research was conducted to determine students' understanding of the impact of smoking on the health of themselves and others, how much support students have for the smoke-free area policy, and what factors influence students' perceptions of smoke-free areas. This research method uses qualitative methods. Conducted at Medan State University with 15 respondents. Respondents are expected to be able to improve the quality of health so they must develop good behavior including knowledge, attitudes and actions. The aim of this research is to describe how students behave and respond to the no-smoking area policy at Medan State University. This study was conducted in September 2024.